Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2ta04797g
|View full text |Cite
|
Sign up to set email alerts
|

MXene/ZnO flexible freestanding film as a dendrite-free support in lithium metal batteries

Abstract: The growth of lithium dendrite during charge/discharge process is one major obstacle for the development of lithium metal batteries. In this work, MXene/ZnO freestanding flexible film was obtained to suppress...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 67 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…(a) Rate performance and (b) cycle performance of lithium-oxygen batteries constructed with 3DM Cu/ZnO@Li-P composite anode. References [43][44][45][46] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…(a) Rate performance and (b) cycle performance of lithium-oxygen batteries constructed with 3DM Cu/ZnO@Li-P composite anode. References [43][44][45][46] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Research has shown that lithium metal prefers to be deposited on materials with low nucleation barriers, such as Au, 95 Pt, 96 Sn, 97 and ZnO. 98 Therefore, the use of these materials to modify the 3D current collector to reduce the nucleation overpotential of lithium is a common method to prolong the initiation of lithium dendrites. However, the deposition of lithium metal tends to be in a "top growth" mode, i.e., the lithium metal prefers to be deposited on the side of the current collector near the diaphragm rather than inside, which not only fails to efficiently utilize the internal space of the 3D structure but also facilitates the growth of lithium dendrites.…”
Section: Gradient Structurementioning
confidence: 99%
“…Research has shown that lithium metal prefers to be deposited on materials with low nucleation barriers, such as Au, 95 Pt, 96 Sn, 97 and ZnO. 98 Therefore, the use of these materials to modify the 3D current collector to reduce the nucleation overpotential of lithium is a common method to prolong the initiation of lithium dendrites. However, the deposition of lithium metal tends to be in a “top growth” mode, i.e.…”
Section: Gradient Structurementioning
confidence: 99%
“…25,26 Recently, the construction of an organic/inorganic artificial SEI has been proven to be a more effective strategy to optimize the interfacial stability of Li/electrolyte due to its synergistic advantages of soft polymer and rigid Li + conductor. 27,28 According to previous reports, flexible polymers such as PVDF, 29 PAN, 30 PDMS, 31 etc. have been used as an artificial SEI to establish an adaptive electrostatic interphase on the surface of Li-metal anode.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, researchers have made great efforts to develop numerous methods to optimize the stability of Li/electrolyte interface, including in situ liquid electrolyte engineering and ex situ artificial SEI. Among them, liquid electrolyte engineering mainly focuses on optimizing solvents, Li salts, high- or low-concentration strategies, and electrolyte additives to realize in situ SEI with ideal organic or inorganic compositions. However, such in situ formed SEI is generally difficult to provide a controllable ideal Li/electrolyte interface to maintain its long-term cycling stability. , In contrast, as an ex situ surface engineering approach, artificial SEI can controllably obtain an ideal Li/electrolyte interface with enhanced Li + conductivity and high mechanical strength for homogeneous Li deposition without dendritic Li growth. , Recently, the construction of an organic/inorganic artificial SEI has been proven to be a more effective strategy to optimize the interfacial stability of Li/electrolyte due to its synergistic advantages of soft polymer and rigid Li + conductor. , According to previous reports, flexible polymers such as PVDF, PAN, PDMS, etc. have been used as an artificial SEI to establish an adaptive electrostatic interphase on the surface of Li-metal anode.…”
Section: Introductionmentioning
confidence: 99%